8. Audio example: Beethoven's Wellingtons Sieg bei Vittoria, op. 91 -- Original version for panharmonicon - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Everett, Nathan (transcriber):::Contributor:::::::::::: (2022)
Wellingtons Sieg bei Vittoria (Wellington's Victory at Vitoria) commemorates the victory of British forces led by the Duke of Wellington over the French army in June 1813 at Vitoria, Spain, which proved to be a turning point in the Peninsular War (1807–1814). The piece is best known today in the version for orchestra, though Beethoven's original version was composed for the Panharmonicon at the invitation of its inventor, Johann Nepomuk Maelzel. News of the victory reached Vienna while Maelzel was residing in the city, where he had befriended Beethoven and had even created a set of ear trumpets for the increasingly deaf composer use as hearing aids. At Maelzel's request, Beethoven composed a commemorative piece that utilized the full range of the Panharmonicon's wind, brass, and percussion instruments and incorporated the British national anthem, "God Save the King." Once the Panharmonicon version was completed, Beethoven and Maelzel saw the potential for a more extensive orchestral version. Beethoven quickly arranged the piece for full orchestra and added a battle sequence that illustrated the events of the battle, including the marching and preparations of both armies and the artillery fire. The orchestral version was premiered in December 1813 at a charity concert for the war wounded. The concert also included the premiere of Beethoven's Seventh Symphony and a performance by Maelzel's mechanical trumpeter, but Wellingtons Sieg was the clear audience favorite.